PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA INDUSTRI PULP AND PAPER YANG TERDAFTAR DIBURSA EFEK INDONESIA - Putri, Eka Jelyta; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine the effect of working capital on profitability padaindustri pulp and paper listed in the Indonesia Stock Exchange. Variable working capital addressed by working capital turnover and profitability demonstrated by Return on Investment (ROI).Data is derived from the financial statements of each company obtained from the Indonesia Stock Exchange which is located street Jl. General Sudirman. The population in this study is the pulp and paper companies listed on the Indonesia Stock Exchange. The sampling method used is purposive sampling and dperoleh sample of three companies taken by pulp and paper companies are experiencing working capital fluctuations that have a financial statement period 2008-2014 in order to obtain 21 observations.Data analysis technique used is simple linear regression. Testing in this research is done using the SPSS version 17. The results of the study showed that the turnover of working capital does not significantly affect the Return On Investment (ROI). Keywords : Working Capital, Working Capital Turnover and Return On Investmnet (ROI)